2021
DOI: 10.1002/nme.6704
|View full text |Cite
|
Sign up to set email alerts
|

Computationally efficient finite element formulation for blood flow analysis in multi‐layered aorta modeled as viscoelastic material

Abstract: In the literature, blood flow study in an arterial segment/arterial network, using one-dimensional wave propagation model, has been carried out considering flat/parabolic/logarithmic/different degree polynomial velocity profile functions. However, such assumptions are not capable of capturing actual blood and arterial wall interaction occurring while the blood flows through the arteries. In this study, a computationally efficient axisymmetric-formulation of the Navier-Stokes equation is presented to eliminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Even though mathematical models of blood circulation frequently neglect the viscous component of the vessel wall, it is well known that blood vessels (and living tissues in general) exhibit viscoelastic properties [45]. Viscoelastic effects are simulated in literature using different (more or less complex) rheological models, whether linear or not [1,22,9,43,19,21,23]. With a simple but still effective choice, we can close system (1) by considering a linear viscoelastic model as representative of the fluidstructure interaction mechanics of blood with the vessel wall.…”
Section: Linear Viscoelastic Constitutive Lawsmentioning
confidence: 99%
“…Even though mathematical models of blood circulation frequently neglect the viscous component of the vessel wall, it is well known that blood vessels (and living tissues in general) exhibit viscoelastic properties [45]. Viscoelastic effects are simulated in literature using different (more or less complex) rheological models, whether linear or not [1,22,9,43,19,21,23]. With a simple but still effective choice, we can close system (1) by considering a linear viscoelastic model as representative of the fluidstructure interaction mechanics of blood with the vessel wall.…”
Section: Linear Viscoelastic Constitutive Lawsmentioning
confidence: 99%
“…Good agreement was found between 3D and 1D solutions, albeit in one case only after manually tuning vessel resistances 38 . Two further studies found good agreement between pressure and flow waveforms at multiple locations in several idealized compliant arterial models, single vessel, bifurcation, aortic arch, and aorta 40,41 . Several studies compared 1D solutions to a 3D whole arterial tree model 42–46 .…”
Section: Introductionmentioning
confidence: 96%
“…38 Two further studies found good agreement between pressure and flow waveforms at multiple locations in several idealized compliant arterial models, single vessel, bifurcation, aortic arch, and aorta. 40,41 Several studies compared 1D solutions to a 3D whole arterial tree model. [42][43][44][45][46] In summary, there was reasonable agreement in larger vessels and healthy scenarios but less in anatomical variations or abnormal hemodynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Z Deng and F Liang constructed a numerical model to simulate stress distribution in the upper arm tissues under an inflatable cuff, and they have found the thickness of the upper arm tissues would significantly damped the transmission of cuff pressure [4]. Hasan et al proposed a novel computationally efficient axisymmetric formulation to simulate hemodynamics behavior accurately in the multi-layered elastic arterial model [5]. Other researchers tried to figure out the standardized calibration for the BP measurement devices.…”
Section: Introductionmentioning
confidence: 99%